Statistical Measures of Affluence: Macroregions in Poland - Wolny-Dominiak, Alicja; Sączewska-Piotrowska, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The paper presents an analysis of the affluence in macroregions of Poland based on statistical measures of income distribution. Research Design & Methods: The analysis uses a group of measures based on the distribution of income in the population studied. The measures characterise a given population in terms of the extent and / or intensity of its affluence. Income inequality and income polarisation are also analysed. All computations are based on European Union Statistics on Income and Living Conditions (EU-SILC) from 2018. Findings: Income affluence is very differentiated across Poland’s macroregions. The Mazowieckie voivodeship macroregion has the highest share of the affluent. All of the other affluence measures likewise show this region to be the most affluent. Implications / Recommendations: Basic measures of income inequality and polarisation give a good initial picture of income affluence but obtaining detailed information about this phenomenon is possible thanks to specific measures of the extent and intensity of income affluence. The results show that affluence is highly differentiated in Poland. Poland’s government would be well-advised to take appropriate measures to encourage entrepreneurs to invest capital in less affluent macroregions. Contribution: The research conducted in this paper shows how to analyse the affluence in subpopulations taking into account the distribution of income. Analysis of income affluence fills the gap in income analyses focusing most of all on poverty. All the statistica measures used provide knowledge about how the affluent greatly influence the economy, policy, and other aspects of life.